2014
DOI: 10.1186/s12964-014-0045-y
|View full text |Cite
|
Sign up to set email alerts
|

miRNAs affect the development of hepatocellular carcinoma via dysregulation of their biogenesis and expression

Abstract: The pathogenesis of hepatocellular carcinoma (HCC) is not fully understood, which has affected the early diagnosis and treatment of HCC and the survival time of patients. MicroRNAs (miRNAs) are a class of evolutionarily conserved small, non-coding RNAs, which regulate the expression of various genes post-transcriptionally. Emerging evidence indicates that the key enzymes involved in the miRNA biosynthesis pathway and some tumor-specific miRNAs are widely deregulated or upregulated in HCC and closely associated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 106 publications
(88 reference statements)
0
20
1
Order By: Relevance
“…Micro RNAs (miRNAs) are small non-coding RNAs involved in several physiological and pathological processes, such as cell growth and differentiation, inflammation, and carcinogenesis by regulating gene expression on a post-transcriptional level [5, 6]. Initially, miRNAs are transcribed as primary miRNAs, processed into precursor miRNAs, and exported to the cytoplasm to form small miRNA duplexes.…”
Section: Introductionmentioning
confidence: 99%
“…Micro RNAs (miRNAs) are small non-coding RNAs involved in several physiological and pathological processes, such as cell growth and differentiation, inflammation, and carcinogenesis by regulating gene expression on a post-transcriptional level [5, 6]. Initially, miRNAs are transcribed as primary miRNAs, processed into precursor miRNAs, and exported to the cytoplasm to form small miRNA duplexes.…”
Section: Introductionmentioning
confidence: 99%
“…MiRNAs are found to be deregulated in most malignancies, affecting carcinogenesis, progression, metastasis and tumor recurrence. In HCC, it has been reported that aberrant expression of let-7 miRNAs contributed to the development and progression of HCC [5, 6]. …”
Section: Introductionmentioning
confidence: 99%
“…Previous researches have shown evidence that miRNAs are involved in various crucial biological processes through imperfect pairing with target mRNAs of protein-coding genes [37,38]. Meta-analysis is used to combine the results based on individual research to yield summary conclusions, especially when results from single case-control studies were incomprehensive and conflicting.…”
Section: Discussionmentioning
confidence: 99%